Makna Simbolik Dupa Dalam Tradisi Mappacci Suku Bugis Kampung Salak Provinsi Papua Barat Daya - Fajrih , Moh Al; Abdullah (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2025)
This study aims to describe the symbolic meaning of incense in the Mappacci tradition of the Bugis people of Salak Village, Southwest Papua Province, and to understand why the Bugis people of Salak Village maintain the symbolic meaning of incense in the Mappacci tradition of the Bugis people of Salak Village, Southwest Papua Province. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The results show that incense in the Mappacci tradition is interpreted as a medium connecting the physical and spiritual worlds, a symbol of the bride and groom's readiness to face a new life, and an expression of gratitude and a request for protection from God Almighty. Furthermore, the presence of incense also reflects the continuity of ancestral values still maintained by the Bugis people amidst the current of modernization. This study emphasizes the importance of preserving cultural symbols as part of the identity and character of the local community.